Poverty Reduction and Growth Trust : Borrowing Agreement with the National Bank of Belgium. (Policy Papers; Policy Paper ;, 2012)
Effective November 12, 2012, the Fund, as Trustee of the Poverty Reduction and Growth Trust (PRGT), entered into a borrowing agreement (the 'Agreement') with the National Bank of Belgium, by which Belgium will provide new loan resources of up to SDR 350 million (see attachment). With this Agreement, the Fund has concluded fourteen new borrowing agreements providing total resources of SDR 9,811 million in the context of fundraising under the 2009 Low-Income Countries (LICs) financing package.